The Challenge of Implementing The Merdeka Campus Program Policy In The Covid-19 Pandemic Period - Paramitha, Yulia Della; Oktaviana, Prita Veronica Putri; Fauzia, Salsabila Azzahra; Kismartini, Kismartini; Herawati, Agustin Rina (Ridwan Institute, 2021)
Education in the 4.0 revolution era is an innovation (student centered) to strengthen creativity and mentality in facing challenges. The challenges during the Covid-19 pandemic require education to use technology assistance. Therefore, the Minister of Education and Culture, Nadiem Makarim, established the Merdeka Campus program policy as a strategic plan for the development of national education. In an effort to implement the Merdeka Campus program, of course, there are challenges during the Covid-19 pandemic. The method used in writing this article is a qualitative approach with the library method. Therefore, the author wants to examine more deeply about the analysis of the challenges of implementing the Merdeka Campus program policy during the Covid-19 pandemic